Datos meteorológicos de la Estación Gonnet del LAyHS (FAU-UNLP) correspondiente al año 2009 - Czajkowski, Jorge Daniel (2010)
Datos meteorológicos de la Estación Gonnet del LAyHS (FAU-UNLP) correspondiente al año 2009.